2019
DOI: 10.1158/0008-5472.can-18-2674
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Interrogation of Human Cancers Identifies EGLN1 Dependency in Clear Cell Ovarian Cancers

Abstract: We hypothesized that candidate dependencies for which there are small molecules that are either approved or in advanced development for a nononcology indication may represent potential therapeutic targets. To test this hypothesis, we performed genome-scale loss-of-function screens in hundreds of cancer cell lines. We found that knockout of EGLN1, which encodes prolyl hydroxylase domain-containing protein 2 (PHD2), reduced the proliferation of a subset of clear cell ovarian cancer cell lines in vitro. EGLN1-dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 55 publications
(91 reference statements)
1
37
1
Order By: Relevance
“…The effect of SMYD2 silencing on cell proliferation was evaluated in the OVTOKO and OVISE cell lines, which have been previously used as representative OCCC cell lines ( 22 , 23 ), using two specific siRNAs against SMYD2. OVTOKO and OVISE cells were transfected with siSMYD2#1, siSMYD2#2 or siNC SMYD2 expression was evaluated using western blot analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of SMYD2 silencing on cell proliferation was evaluated in the OVTOKO and OVISE cell lines, which have been previously used as representative OCCC cell lines ( 22 , 23 ), using two specific siRNAs against SMYD2. OVTOKO and OVISE cells were transfected with siSMYD2#1, siSMYD2#2 or siNC SMYD2 expression was evaluated using western blot analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…FG-4592 was found to have no interference on the initiation, progression, or metastasis of cancer ( Seeley et al., 2017 ). However, recent studies showed an antitumor action of FG-4592 in macrophage-abundant tumors ( Nishide et al., 2019 ), and in human ovarian clear cell carcinoma ES2 cells ( Price et al., 2019 ). In another study, FG-4592 could selectively protect the intestinal tract from radiation toxicity without affecting pancreatic cancer ( Fujimoto et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…HIF inhibitors are currently undergoing the clinical evaluation as anticancer drugs. However, recent studies showed that FG-4592 could inhibit tumor growth of macrophage-abundant tumors ( Nishide et al., 2019 ), and reduced viability and proliferation of human ovarian clear cell carcinoma ES2 cells ( Price et al., 2019 ), suggesting an antitumor potential of FG-4592. In the present study, the role and potential mechanisms of FG-4592 in DOX-induced cardiotoxicity were investigated.…”
Section: Introductionmentioning
confidence: 99%
“…123 This is consistent with the demonstration that HDAC6 inhibition can synergize with anti-PD-L1 therapy in a mouse model, raising the possibility that this combination may represent a novel therapeutic strategy. 124 In early work, prolyl hydroxylase domain-containing protein 2 (PHD2), encoded by EGLN1, has been identified as a potential hypoxia-inducible factor 1α (HIF1A)-dependent therapeutic target in clear cell carcinoma; 125 and screening of ARID1A-deficient cells has suggested that gemcitabine may be an effective therapeutic option in ARID1A-deficient tumors. 126 Post-Treatment Surveillance Current NCCN guidelines do not recommend clear cell carcinomaspecific post-treatment surveillance; 87 patients are followed up in the same way as patients with other histological tumor types.…”
Section: Radiotherapymentioning
confidence: 99%